Contextualising Sharīʿah Economic Law: The Role of Pesantren in Indonesia’s Socio-Legal Landscape - Sofian Al Hakim; Mohamad Sar'an; Ah Fathonih; Agi Attaubah Hidayat (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This article aims to elucidate the resilience of Islamic boarding schools in advancing Sharia economic law. The research employs a descriptive case study methodology using field data and adopting a juridical-empirical approach. Data collection is conducted through observation, interviews, and documentation, while data analysis encompasses data condensation, presentation, and conclusion. The findings indicate that the resilience of Islamic boarding schools in developing Sharia economic law stems from recognizing and strengthening their institutional autonomy. This includes acknowledging the roles of religious leaders, students, and the broader community in developing the pesantren-based Sharia economy. As centers of Sharia economic study and business practice, Islamic boarding schools are poised to serve as pivotal models in translating Sharia economic theory into practice. To enhance their role in this domain, several alternative solutions are proposed: firstly, the formulation of supplementary regulations emphasizing the study of economic law; secondly, the promotion of Islamic boarding schools as exemplars in fostering a Sharia economy within society; thirdly, the integration of Sharia economic law theory into the curriculum to optimize human resource development; and fourthly, the establishment of Islamic boarding schools as Sharia business laboratories capable of engaging in collaborative ventures. The contribution of this study lies in demonstrating how pesantren serve as contextual actors that bridge Islamic jurisprudence and socio-economic practice, offering a model for integrating fiqh al-muʿāmalāt into contemporary legal frameworks. This enriches academic discourse on Islamic law contextualisation while providing practical insights for policymakers, educators, and practitioners in strengthening Sharīʿah economic governance in Indonesia.